Diplomasi Pertahanan Malaysia di Laut China Selatan: Isu dan Tantangan (Malaysia's Defense Diplomacy in the South China Sea: Issues and Challenges) - Sobarini, Eryn; Amalia, Suri; Nurmala, Maharani; Syukur, Moh Abdusy; Wisesa, Raka Gusfi (Universitas Perrtahanan Indonesia (UNHAN), 2021)
The South China Sea dispute has escalated since China claimed 80% of the South China Sea area. This is in conflict with the interests of many countries, one of which is Malaysia. China's claims regarding Malaysia's EEZ area that can endanger Malaysia's national interests. In addition, the United States is also involved in this region and threats to Malaysia come from all sides. This can be a threat to Malaysia's national interest Malaysia is a small country that is building its military strength and relies heavily on trade. In overcoming this threat in the South China Sea, Malaysia seeks to increase mutual trust with related countries, especially China and Malaysia as major countries involved in the SCS region. Malaysia is also consistent in carrying out its foreign policyand actively promotes security in the South China Sea with ASEAN through ASEAN Plus One, ASEAN Regional Forum (ARF), East Asia Summit (EAS), ASEANDefense's Minister Meeting/ASEAN Defense's Minister Meeting-Plus (ADMM/ADMM-Plus) and track II workshops. ASEAN has the same view, which isnot agreeing to China's claims in the South China Sea.